The clearwing moths (Lepidoptera, Sesiidae) of Australia, New Guinea and the Pacific Islands - Kallies, Axel (Zootaxa, 2020)
In this study, the clearwing moths (Sesiidae) of Australia, New Guinea and the Pacific Islands are reviewed. A total of 58 species belonging to 18 genera are recognized as native to this region. This includes the following new species and genera: Lophocnema mackeyi spec. nov. (Australia), Oligophlebia insurgia spec. nov. (New Guinea), Micrecia capillaria spec. nov. (New Guinea), Micrecia kuukuyau spec. nov. (Australia), Micrecia hawkei spec. nov. (Australia), Lamellisphecia sanguinea spec. nov. (New Guinea), Specodoptera hiltoni spec. nov. (New Guinea), Specodoptera hiltoni hibernia spec. nov., ssp. nov. (New Guinea), Aegerosphecia rufea spec. nov. (New Guinea), Melittia flanneryi spec. nov. (New Guinea), Melittia pyroptella spec. nov. (Australia), Archaeosesia milleri gen. nov. et spec. nov. (New Guinea), Nokona kungkay spec. nov. (Australia), Nokona bipora spec. nov. (New Guinea), Pseudosesia muyuae spec. nov. (New Guinea), Pseudosesia sumoensis spec. nov. (New Guinea), Pseudosesia sepikensis spec. nov. (New Guinea), Paranthrenella terminalia spec. nov. (New Guinea), Paranthrenella brandti spec. nov. (New Guinea), Paranthrenella lelatensis sp. nov. (New Guinea). Furthermore, 35 new combinations and each four new generic and species synonyms are introduced, while two genera and three species are resurrected from synonymy. Each 4 taxa at the species and genus levels are considered new synonyms. Six species are listed that originally derive from Africa, Europe, Northern Africa or Central America and were introduced into Australia or some of the Pacific Islands accidentally or deliberately.